Chemical Modifications of Electrospun Non-woven Hydroxypropyl Cellulose Fabrics for Immobilization of Aminoacylase-I (Journal of Fiber Bioengineering and Informatics, 2012)
Because of its wide solubility range, Hydroxypropyl Cellulose (HPC) is suitable for fabricating fine-fibermaterials via electrospinning. The resulting electrospun non-woven fabric (HPC-ESNW) requires anappropriate post-spinning treatment for applications in aqueous environments. In the present study, weexamined the insolubilization of HPC-ESNW via cross-linking using bifunctional isocyanates.Modification of the fine-fiber surfaces with NCO groups enables introduction of cationic functionalities;we found that cationic Diethylaminoethyl (DEAE) groups are suitable for immobilization of aminoacylase-I onto these fine-fiber surfaces under mild conditions. The NCO groups can be also converted to aminogroups, followed by activation with bifunctional N-hydroxysuccinimide (NHS) esters. The NHS-ESNWcan chemically bind the aminoacylase-I. Two kinds of immobilized enzyme were tested for stereospecificrecognition of a substrate and for immobilized activity yields. The results suggest that NCO-ESNW isa multi-purpose intermediate for chemical modification of ESNW and that the hydrophilic HPC-ESNWis a promising material for use as a matrix for enzyme immobilization.